Cat Colony Caretakers' Perceptions of Support and Opposition to TNR - Rand, Jacquie; Hayward, Andrea; Tan, Kuan (Frontiers in Veterinary Science, 2019)
Trap, neuter and return (TNR) is a non-lethal approach to urban cat management used effectively internationally to decrease urban cat numbers, but deemed illegal in Australia. We investigated perceived support and opposition to TNR experienced by respondents involved in TNR activities, as individuals or through organizations. TNR was initiated to reduce cat numbers, as a humane way to manage community cats, and to improve cat welfare. Many respondents sought permission from local authorities, and all received verbal permission. Perceived attitudes of stakeholders, for example authorities and neighbors, were polarized, with some supporting it and others antagonistic and threatening legal action. Respondents generally managed the colony themselves or with assistance from friends or family, and half obtained aid from a cat welfare agency. Some respondents received cash or food from stakeholders, subsidies for desexing and education on trapping. Complaints were most common from neighbors, and less from those working and living nearby the colony. Resolution was attempted with varying success, by face-to-meetings with complainants, educational flyers, cat deterrents or relocating cats. Supportive stakeholders had similar motives to the respondents for supporting TNR, namely to reduce cat populations and improve cat welfare. These findings are important because they demonstrate the difficulty faced by individuals and organizations undertaking TNR in Australia. Given the reported effectiveness of well-managed TNR programs, and the lack of other acceptable methods for managing urban stray cats at a city level, it is recommended that TNR be legalized in Australia in urban and periurban areas to facilitate its implementation.